2006
DOI: 10.1007/s10903-006-6339-9
|View full text |Cite
|
Sign up to set email alerts
|

Health and Related Factors for Sudanese Refugees in Nebraska

Abstract: Results of a health survey covering demographics, health risk/prevention factors, and barriers to health care among 263 refugees from Sudan, now living in Nebraska, are presented. Data are compared to Nebraska's general and minority populations. Sudanese refugees are generally young, highly mobile, uneducated, and live in poverty. Refugees are proportionally different from other Nebraskans, in terms of risk factors and rates of common U.S. conditions, but are unable to use preventive systems for maintaining hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 10 publications
0
28
0
1
Order By: Relevance
“…For instance, some studies utilize instruments similar to the USDA food security assessment tool (Hadley et al 2007), while others rely on a single item measure of food insufficiency (Gallegos et al 2008). Still others use single items that are at best suggestive of food insecurity (Willis and Nkwocha 2006). For example, a study of 263 Sudanese refugees living in Nebraska noted that 58% of the sample reported being "concerned about nutrition or eating" since arriving in the United States (Willis and Nkwocha).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some studies utilize instruments similar to the USDA food security assessment tool (Hadley et al 2007), while others rely on a single item measure of food insufficiency (Gallegos et al 2008). Still others use single items that are at best suggestive of food insecurity (Willis and Nkwocha 2006). For example, a study of 263 Sudanese refugees living in Nebraska noted that 58% of the sample reported being "concerned about nutrition or eating" since arriving in the United States (Willis and Nkwocha).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important for refugees from Sudan as they face very dramatic changes in the relocation from Africa to North America-e.g., air travel to a continent with a wholly different cultural milieu and climate, diverse languages and educational systems, and vastly different legal codes and procedures (Willis & Nkwocha, 2006). Moreover, Sudanese refugees face these dramatic environmental and contextual changes having fled a country at war for more than two decades and having survived lengthy confinement within African refugee camps (U.S. Committee for Refugees, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…S. Department of Health & Human Services, 2003), few refugees receive the training and preparation necessary to navigate U.S. life. Consequently, we asked Dinka and Nuer what they felt was the most important health concern and a majority responded with a request for the permanent replacement of lower front teeth removed through childhood ritual in Sudan (Willis & Nkwocha, 2006). We then designed a dental restoration program that provided the highest quality permanent replacement for the missing anterior teeth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations